Case report: Tolosa-Hunt syndrome—expanding the neuromyelitis optica spectrum disorder phenotype? - Park, Soo-Hyun; Jang, Soo-Im; Lee, Eun-Ja; Kim, Nam-Hee (Frontiers in Neurology, 2024)
Neuromyelitis optica spectrum disorder (NMOSD) is an autoimmune astrocytopathy caused by the autoantibody of aquaporin-4 (AQP4). Herein, we report a case of Tolosa-Hunt syndrome presenting with abducens palsy and AQP4 antibodies. This was a rare case of AQP4-immunoglobulin G seropositivity in a patient with Tolosa-Hunt syndrome. Our findings may expand the clinical phenotype of NMOSD and indicate that clinicians should consider testing for AQP4 antibodies in patients with Tolosa-Hunt syndrome.